A Molecular Level Understanding of Zinc Activation of C-peptide and its Effects on Cellular Communication in the Bloodstream (The Review of Diabetic Studies, 2023)
Inspired by previous reports, our group has recently demonstrated that C-peptide exerts beneficial effects upon interactions with red blood cells (RBCs). These effects can be measured in RBCs obtained from animal models of both type 1 diabetes and type 2 diabetes, though to different extents. To date, the key metrics that have been measured involving C-peptide and RBCs include an increase in glucose uptake by these cells and a subsequent increase in adenosine triphosphate (ATP) release. Importantly, to date, our group has only been able to elicit these beneficial effects when the C-peptide is prepared in the presence of Zn2+. The C-peptide-induced release of ATP is of interest when considering that ATP is a purinergic signaling molecule known to stimulate the production of nitric oxide (NO) in the endothelium and in platelets. This NO production has been shown to participate in smooth muscle relaxation and subsequent vessel dilation. Furthermore, NO is a well-established platelet inhibitor. The objective of this review is to provide information pertaining to C-peptide activity on RBCs. Special attention is paid to the necessity of Zn2+ activation, and the origin of that activation in vivo. Finally, a mechanism is proposed that explains how C-peptide is exerting its effects on other cells in the bloodstream, particularly on endothelial cells and platelets, via its ability to stimulate the release of ATP from RBCs.